![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
b) x2 + 9x + 20 = x2 + 4x + 5x +20 =x(x + 4) + 5(x + 4) = (x + 4)(x+ 5)
a) 7x^2-7y^2-14x+14y= 7 ( x^2 - y^2 ) - 14 ( x+y) = 14 ( 2(x^2) - 2 (x^2))- 28 ( 2x+2y)
= 28 ( 4 ( x^2)-4(y^2))- 28 ( 2x+2y)
= 28 (4(x^2-y^2) - 4(x+y)
= 28 (4( x^2-y^2-x+y ))
= 112 . ( x-y-x+y)
![](https://rs.olm.vn/images/avt/0.png?1311)
B= 2x^2+2x+3x+3
= 2x(x+1)+3(x+1)
=(x+1)( 2x+3)
C=3x^2-6x-x+2
=3x(x-2)-(x-2)
=(x-2)(3x-1)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(g,x^2-2xy+y^2-9z^2=\left(x-y\right)^2-\left(3z\right)^2\)\(=\left(x-y+3z\right)\left(x-y-3z\right)\)
\(h,5x^4-20x^2=5x^2\left(x^2-4\right)=5x^2\left(x-2\right)\left(x+2\right)\)
\(i,7x^2-7y^2-14x+14y=7\left(x-y\right)\left(x+y\right)-14\left(x-y\right)\)
\(=\left(x-y\right)\left(7x+7y-14\right)=7\left(x-y\right)\left(x+y-2\right)\)
\(k,x^2+8x+3x+24=x\left(x+8\right)+3\left(x+8\right)=\left(x+8\right)\left(x+3\right)\)
\(m,x^4-y^4=\left(x^2-y^2\right)\left(x^2+y^2\right)=\left(x-y\right)\left(x+y\right)\left(x^2+y^2\right)\)
\(n,x^6-y^6=\left(x^2-y^2\right)\left(x^4+x^2y^2+y^4\right)=\left(x-y\right)\left(x+y\right)\left(x^4+x^2y^2+y^4\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1)a2(b-c)+b2(c-a)+c2(a-b)
=a2b-a2c+b2c-b2a+c2a-c2b
=(a2b-c2b)+(b2c-b2a)+(c2a-a2c)
=b.(a2-c2)-b2.(a-c)-ac.(a-c)
=b.(a-c)(a+c)-b2(a-c)-ac(a-c)
=(a-c)(ab+bc-b2-ac)
=(a-c)[(ab-ac)+(bc-b2)]
=(a-c)[a.(b-c)-b.(b-c)]
=(a-c)(b-c)(a-b)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\Leftrightarrow ab^2-ac^2+bc^2-ba^2+ca^2-cb^2\)
\(\Leftrightarrow a\left(b^2-c^2-ab+ac\right)+bc^2-b^2c\)
\(\Leftrightarrow a[\left(b-c\right)\left(b+c\right)-a\left(b-c\right)]-bc\left(b-c\right)\)
\(\Leftrightarrow a\left(b-c\right)\left(b+c-a\right)-bc\left(b-c\right)\)
\(\Leftrightarrow\left(b-c\right)\left(ab+ac-a^2-bc\right)\)
\(\Leftrightarrow\left(b-c\right)[a\left(b-a\right)-c\left(b-a\right)]\)
\(\Leftrightarrow\left(b-c\right)\left(a-c\right)\left(b-a\right)\)